2020
DOI: 10.1111/odi.13542
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat and male sex increase histopathological changes in a mouse model of oral cancer

Abstract: Objective To compare the effects of dietary fat and sex on murine oral squamous cell carcinoma pathology. Materials and methods Male and female C57Bl/6 mice (36/sex) received a low‐fat (10 kcal%) or high‐fat (60 kcal%) diet. Water (control), vehicle, or 4‐nitroquinoline‐1‐oxide in vehicle (50 μg/ml) was provided for 17 weeks followed by six additional weeks of water. Oral lesion development was recorded weekly. Histopathologic changes in tongues were examined, and T cells (CD3+), macrophages (CD68+), and neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Therefore, none of the experimental animals developed tumors that, due to their size, would mandate euthanizing the animal. This was further confirmed by the 24-hour food intake measurement performed at week 19 of the study that did not show any significant reduction in calorie consumption in 4NQO-treated when compared to control mice [ 34 ].…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Therefore, none of the experimental animals developed tumors that, due to their size, would mandate euthanizing the animal. This was further confirmed by the 24-hour food intake measurement performed at week 19 of the study that did not show any significant reduction in calorie consumption in 4NQO-treated when compared to control mice [ 34 ].…”
Section: Resultsmentioning
confidence: 76%
“…In this study we aimed to investigate whether administration of the chemical carcinogen 4NQO would cause hepatic pathology in an established mouse model of oral cancer. 4NQO, when administered in the drinking water, caused oral squamous cell carcinoma in all mice that completed the protocol [ 34 ]. This chemical carcinogen causes changes in oral tissues in a manner analogous to changes caused by tobacco exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we aimed to examine the effects of a diet sufficient in dietary folate compared to a diet deficient in dietary folate, as well as the effects of sex on the incidence and severity of oral SCC in the well-characterized 4NQO-induced murine model of oral SCC (Schoop et al, 2009). Previous studies in our laboratory demonstrated the influence of sex and dietary fat intake on 4NQO-induced oral SCC, demonstrating increased total tumor burden in male mice and mice fed a 60 kcal% fat diet compared to female mice and mice fed a 10 kcal% diet (Green et al, 2021). In the current study, immunohistochemistry was used to compare expression of folate transport proteins (reduced folate carrier, folate receptor, and proton-coupled folate transporter), as well as to evaluate cellular proliferation as measured by the presence of Ki67+ cells (Gerdes, 1990).…”
Section: Introductionmentioning
confidence: 91%
“…Consumption of minimally processed foods has been reported as a protective factor in the development of squamous cell carcinoma of the head and neck [98]. An in vivo mouse model demonstrated that a high-fat diet and male sex contribute to the pathology of 4-nitroquinoline-1-oxideinduced oral cancer [99]. An important dietary risk factor for the development of OSCC is the high intake of iron linked to the involvement of this element in major cellular processes, such as metabolism, cell growth, and proliferation, with the generation of nitrogen compounds and free radicals, which cause cell damage [100].…”
Section: Diet and Nutritionmentioning
confidence: 99%